Penggunaan media wordwall dalam meningkatkan motivasi belajar siswa dalam pembelajaran bahasa Arab di MAN Sumenep - Lailiyah, Selviatul (Maliki Interdisciplinary Journal, 2024)
A B S T R A C T This study aims to find out 1) how to use wordwalls in learning Arabic 2) the use of student perceptions of wordwalls in learning Arabic. The background of this research is the lack of interest and motivation of students in learning Arabic apart from the difficulty level of learning Arabic as well as the lack of attractive infrastructure or media for learning Arabic. This research method is a qualitative descriptive approach with direct observation on wordwall media and interviews with class XI students of Sumenep State Islamic Senior High School and documentation. The results of this study are to find out the use of wordwalls in learning and students' perceptions of wordwalls in learning Arabic.